Pengabdian Kepada Masyarakat Melalui Kuliah Kerja Nyata (KKN) Di Kelurahan Besar Kota Medan - Erlina, Lira; Al Fudiah, Nurul; Auliya, Khanna; Shadiqah, Cut Aufia; Fadhillah, Salsabila; Rizki, Nurul Lathifah Komala (Pusat Penelitian dan Pengabdian Masyarakat STIQ ZAD Cianjur, 2023)
One form of community service through real work lectures (KKN) is the contribution of students in overcoming problems that occur in society. This service aims to increase environmental awareness and educate the community through the Al-Qur'an education program in Medan's large villages. The method used in this service is observation. KKN students participated in teaching and learning activities, held Qur'an-based seminars and educated children about the importance of learning the Qur'an. The results of the service show that through KKN, community awareness in improving Qur'anic education has increased significantly. The community began to understand the importance of Qur'an-based education. Children also showed an increase in knowledge about Qur'anic education.